Algebra - Bird, John
Algebra 1 is the first product in the Matrix Mathematics series. This algebraic manipulation engine is unique - it not only calculates the answers to algebraic expressions, but it also shows the working out required to get to the answer. This is to provide a better learning model for mathematics - students can formulate their own problems for the computer and see the worked solutions. The rationale behind this approach is that if students have to formulate a problem then they are one step nearer to understanding the solution. The same engine is also used to score students' answers to the hundreds of question on the CD which means that we are not limited the unreliable multiple choice technique of assessing students - we can actually be intelligent about their answer and score them accordingly. This CD consists of basic operations, laws of indices, brackets & factors, laws of precedence, proportionality and simple equations.